Phenolic composition and antioxidant activity assessment of southeastern and south Brazilian propolis - Coelho, Joana C.M.M. (2018)
Propolis is a resinous substance collected by honey bees Apis mellifera from several plant sources and used in the hive to seal the walls, to strengthen the ends of the honey comb or embalm dead invaders. The chemical specificity of propolis is directly determined by the variability of the plant origins and by geographical and climatic features of the collection site. The aim of this work was the quality assessment of 16 south and southeast Brazilian propolis samples through the identification and quantification of phenolic compounds using chromatographic and spectroscopic techniques such as HPLC and LC/DAD/ESI-MS n . Generally, the samples presented a phenolic profile related to Brazilian green propolis with origin in Baccharis spp. leaves, where the caffeoylquinic ac id derivatives as well as dihydrokaempferide and artepillin C were the main compounds. Moreover, DPPH • free radical-scavenging activity, reducing power and differential pulse voltammetry were applied to evaluate the antioxidant activity. Differential pulse voltammetry proved to be a rapid and easy tool for the quantification of the total electroactive species present in the samples. The results revealed a richer phenolic composition and higher bioactivity in Minas Gerais samples rather than the southern ones.